Content validity determination of the countenance-tri kaya parisudha model evaluation instruments using lawshe's CVR formula - Divayana, D G H; Suyasa, P W A; Adiarta, A (Journal of physics. Conference series, 2020)
Good Instruments that are used as measurement instruments in evaluation process should be valid instruments. An attempt that is made to obtain a valid instrument is to calculate the instrument content validity correctly by using the right formula. One formula that can be used to test the content validity of the Countenance-Tri Kaya Parisudha model evaluation instruments is Lawshe's CVR. Based on those statements, the main objective of this study was to explain how to use the Lawshe's CVR formula to determine the content validity of a Countenance-Tri Kaya Parisudha model evaluation instruments. Subjects that were involved in conducting the trial of the instruments were 15 panellists. The tool that was used to test the instrument was a questionnaire consisting of 30 questions. Analysis of the instruments was done by comparing the results of validation to Guilford standards so that that instrument classification could be determined. These study results indicate that the Countenance-Tri Kaya Parisudha model evaluation instruments were at a high level of validation with the average of content validity ratio 0.644.